The gap between academy and industry - A qualitative study in Turkish aviation context - ERGUN, HANDE SİNEM (ELSEVIER SCI LTD, 2019)
Following the rapid growth of aviation industry in Turkey, the number of universities offering aviation management programs and enrolled students have substantially increased. The aim of these programs is to meet the demand of qualified personnel needed by the growing aviation industry and to contribute to its development. However, the extent to which these departments fulfill their missions is unknown. Universities and industry face different public pressures, regulatory expectations, and industry norms. In addition, both sides have different cultures, policies, and institutional logics. These differences affect how the academy and the industry form and manage their relationship. The aim of this study is to explore the current relationship between Turkish aviation industry and aviation management departments of Turkish universities and to understand how their expectations and values are shaped by the institutional dynamics and institutional logics. The findings reveal that different institutional logics of the aviation industry and aviation management programs result in a gap between what the aviation industry managers value and what aviation management programs offer. This gap causes graduates to face difficulty in finding job in the aviation industry and it also hinders the effective collaboration between industry and academy.
Keywords: Higher education in aviation; Aviation industry; University-industry collaboration; Institutional theory; Institutional logics; INSTITUTIONAL LOGICS; KNOWLEDGE TRANSFER; UNIVERSITY; ORGANIZATIONS; POWER; COLLABORATION; COMPLEXITY; RESPONSES; CHANNELS; IMPACT